Tundra Discoveries - Wadsworth, Ginger (Watertown, MA : Charlesbridge Publishing, 1999)
Describes the behavior of thirteen different animals, including caribou, arctic foxes, lemmings and owls, during one full year on the artic tundra.
Keywords: Animals